Do capital participation and omzet increase the profit of Village-Owned Enterprises? - Azhari, Azhari (Politeknik Negeri Batam, 2024)
Capital participation and omzet are considered important factors that affect the financial performance ofBUMDES (Village-owned enterprises), especially the profits generated. This study aims to examine the effect of capital participation and omzet on BUMDES profits. The method used is secondary data analysis and survey of BUMDES in Aceh Province, Indonesia. Data is taken from BUMDES' financial statements and survey results that ask about capital participation, omzet, and profit. Descriptive statistical analysis and multiple linear regression are used to analyze the data. The results showed that capital participation has a positive influence on BUMDES' profits. Greater capital participation gives BUMDES greater capital to develop their business, which in turn can increase revenue and profits. In addition, omzet also has a positive influence on BUMDES' profits. The practical implication of this research is the importance of the government and other stakeholders to support capital participation and increase the omzet of BUMDES as a strategy to improve the economic welfare of rural communities.